2005
DOI: 10.1021/ja042898o
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Protein Adsorption:  Surface-Induced Conformational Changes

Abstract: Protein adhesion plays a major role in determining the biocompatibility of materials. The first stage of implant integration is the adhesion of protein followed by cell attachment. Surface modification of implants (surface chemistry and topography) to induce and control protein and cell adhesion is currently of great interest. This communication presents data on protein adsorption (bovine serum albumin and fibrinogen) onto model hydrophobic (CH(3)) and hydrophilic (OH) surfaces, investigated using a quartz cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

83
1,216
0
10

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,314 publications
(1,337 citation statements)
references
References 32 publications
83
1,216
0
10
Order By: Relevance
“…This eventually results in an alignment of the proteins across the ripple backbones, which increases the contact area between neighboring proteins. Protein-protein interaction leading to an increased surface coverage is also described by Roach et al [3]. Although we observed the described adsorption behavior on short-wavelength ripples only on Si surfaces, we assume a similar effect for TiO 2 .…”
Section: Protein Adsorptionsupporting
confidence: 79%
See 1 more Smart Citation
“…This eventually results in an alignment of the proteins across the ripple backbones, which increases the contact area between neighboring proteins. Protein-protein interaction leading to an increased surface coverage is also described by Roach et al [3]. Although we observed the described adsorption behavior on short-wavelength ripples only on Si surfaces, we assume a similar effect for TiO 2 .…”
Section: Protein Adsorptionsupporting
confidence: 79%
“…This in turn is mediated by protein adsorption on the surface of the corresponding device [1][2][3]. An improvement and acceleration of the healing after surgical intervention would cause a tremendous enhancement of life quality.…”
Section: Introductionmentioning
confidence: 99%
“…There has, however, been relatively few reports on protein adsorption measurements on highly hydrophobic or superhydrophobic (h [ 150°) surfaces. Some researchers report on the adsorption of protein on superhydrophobic surfaces [18] while some report on non-adsorbent properties on these surfaces [19,20]. Roach et al studied the interaction of proteins on hydrophilic and superhydrophobic porous thermally modified silica [20].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers report on the adsorption of protein on superhydrophobic surfaces [18] while some report on non-adsorbent properties on these surfaces [19,20]. Roach et al studied the interaction of proteins on hydrophilic and superhydrophobic porous thermally modified silica [20]. In their study a reduction in the level of BSA adsorption was observed on the superhydrophobic silica substrate material when compared with hydrophilic substrates.…”
Section: Introductionmentioning
confidence: 99%
“…7 The adsorption of proteins to lipid layers is recognized as the first event following the implantation of biomaterials and has been shown to play an important role in determining subsequent events such as thrombus formation, foreign body reaction, and other undesirable responses. 8,9 The function of proteins is realized by their residues, whose capability is greatly affected by their local environment. It is of great importance to study the distribution of proteins in lipid membranes.…”
Section: Introductionmentioning
confidence: 99%